COMPREHENSIVE MODEL OF PROTECTION AND RESCUE IN PREVENTIVE URBAN SECURITY (Annual of the Faculty of Philosophy in Skopje, 2020)
In recent decades, the frequency of natural and anthropogenic accidents has increasedworldwide. The large unplanned expansion of cities to accommodate rapidpopulation growth, combined with unplanned field use and the failure of city governmentsto regulate building standards, contributes to the vulnerability of urban populations.The author attempts to point out the need to apply a comprehensive model ofProtection and Rescue because current models and concepts are limited to the tasksthat they theoretically conceptually include as well as the time phases in which theyoperate in the event of an accident. The solution is in the comprehensive Civil DefenceEmergency Management Model, whose assessment of numerous accident risks relatesto the process of identifying the occurrence, probability, and assumption of potentiallikelihood of different types of accidents within a general spatial and temporal frameworkof cities.
Keywords: ACCIDENTS; URBAN DEVELOPMENT; ACCIDENT PREPARATION; PROTECTION AND RESCUE; VULNERABILITY